Reentry: challenges, collateral consequences, and advocacy for returning community members - Sommers, Carly (Handbook of forensic social work, 2024)
Reentry into the general population after being incarcerated presents many difficulties, such as finding housing, shelter, and support. Recidivism rates continue to be high, and people often are rearrested within nine years of being released. Formerly incarcerated people often struggle with the stigma surrounding those who have been incarcerated, and this often leads to difficulties finding housing, jobs, and government funding. Advocating for enhancing community resources for those who are reentering society after being incarcerated can change the outcome of their futures. Instead of focusing funding solely on the policing and court side of the criminal justice system, investing in substance use and mental health prevention and treatment can help reentry success. This chapter covers the difficulties of reentry, the stigma surrounding incarcerated people, and ways to advocate for change to make reentry more successful.